2014
DOI: 10.1021/ma500905n
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Chain Architecture in Acrylic Block Terpolymers

Abstract: In this article, we report the manipulation of block terpolymer morphology through control of the segment distribution. We consider a model system comprised of three acrylic monomers: hydrophilic poly(hydroxyethyl acrylate) (H), hydrophobic poly(octyl acrylate) (O), and polar poly(methyl acrylate) (M). For each of four chemical compositions, we altered the M segment distribution in four terpolymer architectures with reversible addition–fragmentation chain transfer (RAFT) polymerization to yield: two triblock t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Hyperbranched poly­(AESO)­s (PAESOs) were synthesized via different conditions spanning a range of monomer and initiator concentrations. ETMP as the CTA was selected in this study due to its good control of acrylic monomers, studied extensively by Bergman et al , While it is known that xanthates with R groups featuring secondary carbons struggle to mediate RAFT polymerizations, we have found that xanthates that use R groups with tertiary carbon are efficacious for acrylic monomers. The proper rate of addition–fragmentation of ETMP ensures equal probability of all chain growth, minimizing the chances of network formation by uncontrolled free radical polymerization .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperbranched poly­(AESO)­s (PAESOs) were synthesized via different conditions spanning a range of monomer and initiator concentrations. ETMP as the CTA was selected in this study due to its good control of acrylic monomers, studied extensively by Bergman et al , While it is known that xanthates with R groups featuring secondary carbons struggle to mediate RAFT polymerizations, we have found that xanthates that use R groups with tertiary carbon are efficacious for acrylic monomers. The proper rate of addition–fragmentation of ETMP ensures equal probability of all chain growth, minimizing the chances of network formation by uncontrolled free radical polymerization .…”
Section: Resultsmentioning
confidence: 99%
“…Chain Transfer Agent Synthesis. Ethyl 2-(ethoxycarbonothioylthio)-2-methylpropanoate (ETMP) was synthesized following the method reported by Bergman et al 41,42 Potassium hydroxide (50 mmol) was stirred in ethanol (20 mL) at room temperature until it completely dissolved. Then carbon disulfide (10 mL) was added over 90 min, and the solution was allowed to stir for 5 h. Ethyl αbromoisobutyrate (14.8 mL) was added dropwise, and the solution was stirred for 12 h. The mixture was filtered and solvent was removed by rotary evaporation.…”
Section: Biomacromoleculesmentioning
confidence: 99%
“…Experimental gel conversions X g,exp (filled symbols) and Flory–Stockmeyer predicted gel conversions X g FS (opened symbols) vs crosslinking tendency for this work (▼, ▽), our previous work of poly­(acrylated epoxidized soybean oil) (PAESO) (▲, △), other RAFT (◆, ◇), and ATRP (●, ○) in the literature. , X g FS is calculated based on eq . The experimental gel conversions in region I are related to CT by X g,exp = 141.65 – 60 log­(CT) with r 2 = 0.85.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure below is analogous to the method described by Bergman et al (31) Potassium hydroxide (0.05 mol) was stirred in ethanol (20 mL) at room temperature until completely dissolved. Carbon disulfide (10 mL) was then added over 90 minutes, and the solution was allowed to stir for five hours.…”
Section: Chain Transfer Agent Synthesismentioning
confidence: 99%